(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: The prevalence of obesity and Metabolic Syndrome (MS) has increased globally, leading to Non Alcoholic Fatty Liver Disease (NAFLD) becoming the most prevalent liver disorder worldwide. Various studies have indicated that Waist Circumference (WC) serves as a surrogate marker for visceral fat accumulation, while waist-hip ratio is suggested as a superior screening tool for NAFLD compared to Body Mass Index (BMI). The objective of this study was to assess the correlation between anthropometric indices and Insulin Resistance (IR) in NAFLD patients at Chittagong Medical College Hospital (CMCH). Materials and methods: This cross-sectional study was conducted at the Department of Biochemistry, Institute of Nuclear Medicine and Allied Sciences (INMAS) in collaboration with Chittagong Medical College Hospital (CMCH). One hundred and fifty (150) subjects aged between 18-60 years were enrolled using a non-probability consecutive sampling method. NAFLD subjects were identified through ultrasonography and detailed anthropometric measurements were recorded. IR was evaluated using the Homeostatic Model Assessment of Insulin Resistance (HOMA-IR). Results: Among the NAFLD subjects, 81.3% were classified as obese. The BMI of NAFLD subjects was significantly higher compared to non-NAFLD subjects (26.60±0.29 vs. 21.15 ± 0.25 kg/m2). Furthermore, 90% of NAFLD subjects exhibited central obesity, as indicated by WC. Regardless of gender, NAFLD subjects demonstrated significantly higher WC and waist-hip ratios. IR (HOMA-IR > 2.6) was more prevalent among obese NAFLD subjects (94% vs. 77%). Conclusions: BMI, WC, and Waist-Hip Ratio are associated with IR in NAFLD patients, suggesting their utility in predicting NAFLD. JCMCTA 2024 ; 35 (1) : 77-81